Microencapsulation of roasted coffee oil Pickering emulsions using spray- and freeze-drying: physical, structural and in vitro bioaccessibility studies - Franco Ribeiro, Elisa [UNESP]; Carregari Polachini, Tiago [UNESP]; Dutra Alvim, Izabela; Quiles, Amparo; Hernando, Isabel; Nicoletti, Vania Regina [UNESP] (Oxford University Press (OUP), 2022)
Microcapsules produced from well-defined emulsion templates are an interesting alternative for lipid encapsulation. This work aimed to produce microcapsules by the freeze-drying (FD) and spray-drying (SD) of Pickering emulsions of roasted coffee oil (RCO) stabilised with chitosan nanoparticles produced by self-aggregation or by crosslinking with tripolyphosphate. The dried microcapsules were characterised in terms of particle size, oil retention and structure; furthermore, the in vitro bioaccessibility of polyphenols from microencapsulated RCO was investigated. The use of chitosan nanoparticles to stabilise the emulsions increased oil retention in the microcapsules giving values between 83.04% and 95.36%. SD produced spherical microcapsules with small particle sizes (˜11 μm), whereas FD microcapsules showed an irregular shape and porous structure. Although FD had the lowest impact on the bioactive compounds, SD promoted better protection for phenolic compounds and antioxidant activity during in vitro digestion.
Keywords: Antioxidant activity; bioactive compounds; chitosan nanoparticles; in vitro digestion; lipid encapsulation; phenolic content